Guidelines for the early management of patients with myocardial infarction. British Heart Foundation Working Group. - Weston, C. F. (BMJ Group, 1994)
In light of recent publications relating to resuscitation and pre-hospital treatment of patients suffering acute myocardial infarction of British Heart Foundation convened a working group to prepare guidelines outlining the responsibilities of general practitioners, ambulance services, and admitting hospitals. The guidelines emphasise the importance of the rapid provision of basic and advanced life support; adequate analgesia; accurate diagnosis; and, when indicted, thrombolytic treatment. The working group developed a standard whereby patients with acute myocardial infarction should receive thrombolysis, when appropriate, within 90 minutes of alerting the medical or ambulance service--the call to needle time. Depending on local circumstances, achieving this standard may involve direct admissions to coronary care units, "fast track" assessments in emergency departments, or pre-hospital thrombolytic treatment started by properly equipped and trained general practitioners.